Trauma and General Health: PTSD symptoms and threat appraisal - Heiða Ingólfsdóttir 1991- (2019)
Exposure to traumatic events is common and can have both negative psychological and physiological consequences, adversely affecting the well-being of those exposed. The SAGA cohort study is a unique nationwide study on the impact of trauma on women’s health. The study presents an ideal opportunity to investigate the association of trauma and general health among women. The purpose of this study was to assess the association between traumatic events and adverse health outcomes among women and to examine whether a probable posttraumatic stress disorder (PTSD) diagnosis, subclusters of PTSD (e.g., hyperarousal) or perceived life or social threat of the traumatic event mediate this relationship. Participants were women 18 years and older (n=29,666) currently residing in Iceland who answered a self-report questionnaire assessing socio-demographic data, lifetime history of exposure to traumatic events (The Life Events Checklist for DSM-5 (LEC-5)) and adverse health outcomes (The PTSD Checklist for DSM-5 (PCL-5); Patient Health Questionnaire (PHQ-15)). Results revealed that trauma exposure is associated with adverse health outcomes (PHQ-15 ≥ 15), with the risk of adverse health outcomes increasing in relation to number of traumas experienced. A likely PTSD diagnosis (PCL-5 ≥33) partly mediated the relationship between traumatic exposure and adverse health outcomes. Furthermore, hyperarousal symptoms were the strongest predictor of adverse health outcomes. In addition, the greatest risk of adverse health outcomes was among those who percieved both severe social threat and severe threat to life. These findings may have important implications for theoretical models of PTSD and the conceptualization of trauma as well as clinical implications, e.g. highlighting the need to screen for trauma history in the health care system.